1985
DOI: 10.1007/bf00687803
|View full text |Cite
|
Sign up to set email alerts
|

Spread and distribution of viral antigen in nervous canine distemper

Abstract: Canine distemper virus (CDV) antigen was demonstrated immunocytochemically in the central nervous system (CNS) of 19 dogs killed from 16 to 170 days after infection. In the earliest lesions, infection of glial cells preceded demyelination, and the degree of myelin destruction correlated with the amount of viral antigen in the tissue. It was concluded that initial demyelination in distemper is directly viral-induced, but the nature of the infected glial cells remains uncertain. Ependymal infection and spread of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
57
0
2

Year Published

1990
1990
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 14 publications
6
57
0
2
Order By: Relevance
“…Around 3 weeks after infection, CDV-positive glial cells and neurons are found in the white matter, and the beginning of demyelination is observed in these regions (41). The CNS infection peaks 4 to 5 weeks after inoculation, when virus is detected in neurons and glial cells throughout white and gray matter in a focal fashion (23,45,52). Around 10% of dogs die at this time from acute encephalitis developing while their immune system fails to control the infection.…”
mentioning
confidence: 99%
“…Around 3 weeks after infection, CDV-positive glial cells and neurons are found in the white matter, and the beginning of demyelination is observed in these regions (41). The CNS infection peaks 4 to 5 weeks after inoculation, when virus is detected in neurons and glial cells throughout white and gray matter in a focal fashion (23,45,52). Around 10% of dogs die at this time from acute encephalitis developing while their immune system fails to control the infection.…”
mentioning
confidence: 99%
“…Double labeling-immunohistochemistry has been used to detect viral antigen and GFAP in astrocytes present in, or derived from, brain tissues of CDVinfected animals. In vitro-infected primary cultures have also been examined (25,54,56). An overall decrease has been observed, both in vivo and in vitro, in the numbers of GFAPpositive cells, the prevalence of astrocytic processes, and GFAP staining in some cells (53,57).…”
Section: Vol 74 2000 Notes 3877mentioning
confidence: 99%
“…CDV occur a multifocal demyelinating disease (21). Initial demyelination in distemper encephalitis is directly virus induced (21,23). Demyelination in distemper is thought to be due to a selective alteration of the oligodendrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis was discussed as a possible mechanism of oligodendrocytes loss in demyelinating diseases, and oligodendrocytes were shown to undergo apoptosis after various stimuli in vitro (17). Vandevelde et all (21) reported that granular cells of the cerebellum were dyed in apoptosis. Those areas with several apoptotic granular cells were surrounded by white matter with demyelinated plaques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation